1991
DOI: 10.1017/s014271640000922x
|View full text |Cite
|
Sign up to set email alerts
|

Narrative as an index of communicative competence in mildly mentally retarded children

Abstract: This study compared the narrative abilities of mildly mentally retarded and nonretarded children. Twenty mildly mentally retarded children and 20 nonretarded children, matched on mental age, PPVT-R scores, and SES were audiotaped while narrating a wordless picture book story. Results showed no differences between the groups in narrative length, use of tense and conjunctions, and use of narrative devices. However, there were significant differences in use of reference, with the mildly retarded children using mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 33 publications
2
30
0
1
Order By: Relevance
“…Referencing: Each referral to the characters in the story was tallied and coded as either an appropriate or inappropriate reference. Following previous work on referencing (Hemphill, Picardi, & Tager-Flusberg, 1991;McCabe & Bliss, 2003), the use of pronouns without prior introduction of the characters, repetition of full noun phrases in marking anaphoric references, and the use of incorrect pronouns (i.e., the use of "he" to refer to a female character) were characterized as inappro* priate references. The score for referencing for each narrative was computed by subtracting the total number of inappropriate references from the total number of referential expressions used in the whole narrative.…”
Section: Transcription and Codingmentioning
confidence: 98%
“…Referencing: Each referral to the characters in the story was tallied and coded as either an appropriate or inappropriate reference. Following previous work on referencing (Hemphill, Picardi, & Tager-Flusberg, 1991;McCabe & Bliss, 2003), the use of pronouns without prior introduction of the characters, repetition of full noun phrases in marking anaphoric references, and the use of incorrect pronouns (i.e., the use of "he" to refer to a female character) were characterized as inappro* priate references. The score for referencing for each narrative was computed by subtracting the total number of inappropriate references from the total number of referential expressions used in the whole narrative.…”
Section: Transcription and Codingmentioning
confidence: 98%
“…Thus, the Korean EFL learners' over-reliance on noun phrases observed in the quantitative analysis may seem inappropriate or redundant. However, past research has suggested the use of noun phrases by NES, even after the referents are introduced, is often motivated by specific discourse purposes (Clancy, 1980;Fox, 1987;Hemphill et al, 1991). Therefore, it may be necessary to compare such cases in both Korean EFL learners' and NES' narratives to examine whether the Koreans' use of noun phrases are indeed a simple overuse influenced by their L1 or a reproduction of NES' mature narrative discourse.…”
Section: Qualitative Analysismentioning
confidence: 99%
“…Thus, they mainly used a nominal strategy (Hemphill et al, 1991) in which full noun phrases are used significantly more than pronouns whether or not the focus on the third-person referents is maintained. The following examples best characterize this tendency:…”
Section: The Koreans' Use Of Non-obligatory Noun Phrases In Their L1 mentioning
confidence: 99%
See 2 more Smart Citations